Answer:
Converting the equation
into completing the square method we get: ![\mathbf{(x-10)^2=87}](https://tex.z-dn.net/?f=%5Cmathbf%7B%28x-10%29%5E2%3D87%7D)
Step-by-step explanation:
we are given quadratic equation: ![x^2-20x+13=0](https://tex.z-dn.net/?f=x%5E2-20x%2B13%3D0)
And we need to convert it into completing the square method.
Completing the square method is of form: ![a^2-2ab+b^2=(a-b)^2](https://tex.z-dn.net/?f=a%5E2-2ab%2Bb%5E2%3D%28a-b%29%5E2)
Looking at the given equation ![x^2-20x+13=0](https://tex.z-dn.net/?f=x%5E2-20x%2B13%3D0)
We have a = x
then we have middle term 20x that can be written in form of 2ab So, we have a=x and b=? Multiplying 10 with 2 we get 20 so, we can say that b = 20
So, 20x in form of 2ab can be written as: 2(x)(10)
So, we need to add and subtract (10)^2 on both sides
![x^2-20x+13=0\\x^2-2(x)(10)+(10)^2-(10)^2+13=0\\(x^2-2(x)(10)+(10)^2) \:can\: be\: written\: as\: (x-10)^2 \\(x-10)^2-100+13=0\\(x-10)^2-87=0\\(x-10)^2=87](https://tex.z-dn.net/?f=x%5E2-20x%2B13%3D0%5C%5Cx%5E2-2%28x%29%2810%29%2B%2810%29%5E2-%2810%29%5E2%2B13%3D0%5C%5C%28x%5E2-2%28x%29%2810%29%2B%2810%29%5E2%29%20%5C%3Acan%5C%3A%20be%5C%3A%20written%5C%3A%20as%5C%3A%20%28x-10%29%5E2%20%5C%5C%28x-10%29%5E2-100%2B13%3D0%5C%5C%28x-10%29%5E2-87%3D0%5C%5C%28x-10%29%5E2%3D87)
So, converting the equation
into completing the square method we get: ![\mathbf{(x-10)^2=87}](https://tex.z-dn.net/?f=%5Cmathbf%7B%28x-10%29%5E2%3D87%7D)
Answer:
0,-2,-4
Step-by-step explanation:
Answer: 2
Step-by-step explanation:
The answer would be 10.5 in decimal form. In fraction form you could reduce 6 and 4 and make the six a 3 and make the four a 2. Then multiply it out. Which would be 3/1 multiplied by 7/2 = 21/2